2019
DOI: 10.1002/glia.23665
|View full text |Cite
|
Sign up to set email alerts
|

Myelinated axon physiology and regulation of neural circuit function

Abstract: The study of structural and functional plasticity in the central nervous system (CNS) to date has focused primarily on that of neurons and synapses. However, more recent studies implicate glial cells as key regulators of neural circuit function. Among these, the myelinating glia of the CNS, oligodendrocytes, have been shown to be responsive to extrinsic signals including neuronal activity, and in turn, tune neurophysiological function. Due to the fact that myelin fundamentally alters the conduction properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 149 publications
(202 reference statements)
2
74
0
4
Order By: Relevance
“…Accordingly, we found that myelinated fibers of DBA had smaller axon diameters and thinner myelin. The diameter of myelinated axons is a well-known feature that influences the speed of signal transduction in axons [54]. Interestingly, smaller caliber myelinated fibers are reported for mutant mice for each of the myelin proteins that we observed which are lower expressed in DBA mice: MAG, MOBP and CNP [52,[60][61][62], which is in line with the established concept that proper myelination provides, as well as insulation, also trophic support for axons, thereby increasing axon caliber [2].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Accordingly, we found that myelinated fibers of DBA had smaller axon diameters and thinner myelin. The diameter of myelinated axons is a well-known feature that influences the speed of signal transduction in axons [54]. Interestingly, smaller caliber myelinated fibers are reported for mutant mice for each of the myelin proteins that we observed which are lower expressed in DBA mice: MAG, MOBP and CNP [52,[60][61][62], which is in line with the established concept that proper myelination provides, as well as insulation, also trophic support for axons, thereby increasing axon caliber [2].…”
Section: Discussionsupporting
confidence: 89%
“…To further investigate myelin protein differences between C57 and DBA at 2 months of age, EM analysis was performed on optic nerves, a CNS structure in which all axons are myelinated, making it possible to determine small differences in CNS myelination ( Figure 5) [1,2,50,[52][53][54]. No differences in g-ratio were found between C57 and DBA, whereas the myelin thickness was smaller in DBA compared with C57 ( Figure 5).…”
Section: Electron Microscopy (Em) Reveals Smaller Myelinated Fibers Imentioning
confidence: 99%
“…For example, it has been proposed that electrical conduction through the periaxonal space between the axon and the overlying myelin sheath also contributes to the fundamental nature of conduction along myelinated axons ( Cohen et al, 2020 ). Indeed, numerous ion channels, transporters, and neurotransmitter receptors are present at the axon–myelin interface and are thus well placed to regulate myelinated axon physiology, structure, and integrity ( Suminaite et al, 2019 ). These include axonal ion channels, including potassium (K + ) channels, that extrude ions into the periaxonal space upon neuronal activity and channels in the juxtaposed myelin sheath that buffer ions, including K + , from the periaxonal space ( Rash et al, 2016 ; Wang et al, 1993 ; Schirmer et al, 2018 ; Larson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…During development, the number of myelin lamellae increases from 0 before birth to maximal levels before sexual maturity (Berthold and Carlstedt, 1982). The myelin thickness also depends on electrical activity (Kaller et al, 2017;Suminaite et al, 2019). Therefore, our model suggests that ADFs spatial extent may increase during the development and vary as a function of neuronal electrical activity.…”
Section: Myelination Parametersmentioning
confidence: 84%